Percolation on feature-enriched interconnected systems - Oriol Artime (Nature Portfolio, 2021)
Network robustness is usually assessed following topological criteria, but disregards the role played by non-topological information. Artime et al. propose a flexible percolation framework that overcomes this limitation and combines both dimensions, offering new ways to protect real systems.